On a second species of Envia Ott & Höfer, 2003 (Araneae, Microstigmatidae), with notes on the sympatric type species - Miglio, Laura Tavares; Bonaldo, Alexandre Bragio (Zootaxa, 2011)
A second species of the microstigmatid spider genus Envia Ott & Höfer, 2003 is described from Manaus, Amazonas, Brazil. A new diagnosis, new records and notes on intra-specific variation in the tibial apophysis of the first leg of the male Envia garciai Ott & Höfer, 2003 are also provided. Males of Envia moleque n. sp. are readily recognizable by the copulatory bulb with a strong apical spine on weakly differentiated paraembolic apophysis and by tibia I lacking an apophysis, which is instead represented by a modified retroventral apical spine in the type species. Females can be recognized by the spermathecae with globose distal receptaculum. Both known species in the genus are sympatric at least at the UFAM Experimental Farm, Manaus, Amazonas, Brazil, the type locality of the new species.